Perancangan Aplikasi Sistem Informasi Perusahaan Ekspedisi Logistik PT XYZ Berbasis Web - Lord Maxie Millenito; Erick Fernando (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
In this research, the problem is formulated on how to design an information system for a Logistics expedition company PT XYZ which can provide convenience in carrying out transaction entry processes (Receipts) and also designing dashboards. While the purpose of this research is to find out how to create and design a courier & cargo management system, to find out the number of sales and transactions of PT XYZ through the sales dashboard. The design of this information system uses the Agile Method, which uses a short development cycle, and also does not require large resources and also by using agile methods the manufacturing process becomes more focused and focused. The design of the PT XYZ web-based logistics expedition company information system application can help the company to carry out the process of making receipts and user management and helping the company to see data that has been processed and has been sorted into information through the dashboard, and also the latest historical status of receipts.